A Surgical Framework for the Management of Incomplete Axillary Nerve Injuries - Chi, David; Ha, Austin Y.; Alotaibi, Fawaz; Pripotnev, Stahs; Patterson, Brendan C. M.; Fongsri, Warangkana; Gouda, Mahmoud; Kahn, Lorna C.; Mackinnon, Susan E. (Journal of Reconstructive Microsurgery, 2023)
Background Axillary nerve injury is the most common nerve injury affecting shoulder function. Nerve repair, grafting, and/or end-to-end nerve transfers are used to reconstruct complete neurotmetic axillary nerve injuries. While many incomplete axillary nerve injuries self-resolve, axonotmetic injuries are unpredictable, and incomplete recovery occurs. Similarly, recovery may be further inhibited by superimposed compression neuropathy at the quadrangular space. The current framework for managing incomplete axillary injuries typically does not include surgery.Methods This study is a retrospective analysis of 23 consecutive patients with incomplete axillary nerve palsy who underwent quadrangular space decompression with additional selective medial triceps to axillary end-to-side nerve transfers in 7 patients between 2015 and 2019. Primary outcome variables included the proportion of patients with shoulder abduction M3 or greater as measured on the Medical Research Council (MRC) scale, and shoulder pain measured on a Visual Analogue Scale (VAS). Secondary outcome variables included pre- and postoperative Disabilities of the Arm, Shoulder, and Hand Questionnaire (DASH) scores.Results A total of 23 patients met the inclusion criteria and underwent nerve surgery a mean 10.7 months after injury. Nineteen (83%) patients achieved MRC grade 3 shoulder abduction or greater after intervention, compared with only 4 (17%) patients preoperatively (p = 0.001). There was a significant decrease in VAS shoulder pain scores of 4.2 ± 2.5 preoperatively to 1.9 ± 2.4 postoperatively (p < 0.001). The DASH scores also decreased significantly from 48.8 ± 19.0 preoperatively to 30.7 ± 20.4 postoperatively (p < 0.001). Total follow-up was 17.3 ± 4.3 months.Conclusion A surgical framework is presented for the appropriate diagnosis and surgical management of incomplete axillary nerve injury. Quadrangular space decompression with or without selective medial triceps to axillary end-to-side nerve transfers is associated with improvement in shoulder abduction strength, pain, and DASH scores in patients with incomplete axillary nerve palsy.
Keywords: axillary nerve palsy; quadrangular space; nerve decompression; nerve transfer